Attention and concentration in normal and deaf gamers - Teixeira, Ana (2018)
In this research the performance of individuals with normal hearing and impaired hearing while playing a computer game was evaluated. The aim was to study and understand if impaired hearing gamers are at disadvantage when playing games without being able to hear the music. Three levels (attention, concentration and blinking) were measured to compare and understand how sound can influence players’ attention and concentration performance. The data was recorded using Mindwave equipment during the game Outlast considering two scenarios: game with sound and game without sound. The results show that hearing impaired individuals have the same standard of attention and level of concentration as individuals with normal hearing when there is sound in the game. In the case of the blinking level, this is quite different between the scenarios and the analyzed groups. For this particular study the results suggest that sound is not an important level in the attention and concentration performance of impaired hearing players. Although much work still needs to be done, there is evidence of a relation between the attention and the concentration levels between normal hearing and impaired hearing individuals in the presence and absence of sound.